The Relationship Imports and Exports in Free Zones Have with Türkiye’s Foreign Trade and Employment: The Fourier Autoregressive Distributive Lag (ADL) Hidden Cointegration Test - Müge Seda Ateş; Gizem Ateş; Demet Toktaş; Esra Canpolat Gökçe (İstanbul İktisat Dergisi)
Free zones, which are implemented as a development policy on the basis of the objectives of increasing exports, investments, and employment, facilitating imports, contributing to domestic production, ensuring technology transfer, and balancing regional differences, are special areas where tax advantages are offered to companies. The aim of this study is to investigate the level of contribution of firms supported by tax advantages in Türkiye’s free zones to Türkiye’s foreign trade and employment and to investigate the relationship between these variables. Within this framework, data compiled for monthly periods between 2013.01-2022.05 were used. The Fourier ADL hidden cointegration test was conducted by constructing 7 different models with the identified variables. In the study, it is reported that the contribution of free zones import-export with tax advantages to Türkiye’s foreign trade and employment mechanism is weak. In this framework, it has been tried to present policy recommendations for taxation, foreign trade, and employment based on the principles of both integrating free zones into international trade and achieving a more collaborative, innovative, and qualified structure to eliminate regional differences in local economies.